Proposed new interior design scheme of craft gallery at No 118, Lorong Maarof, Taman Bangsar Baru, 59000 Kuala Lumpur for Roshfin's Keramik / Raja Nur Aqilah Raja Mustafa Kamal - Raja Mustafa Kamal, Raja Nur Aqilah (Faculty of Architecture, Planning and Surveying, 2012)
The purpose of this research was to implement and evaluate by proposed a new interior design scheme of craft gallery for Roshfin Keramik. It also get response by using a design issue problem through interview. The participant from this interview was executive director of Roshfin Keramik gallery and their gener5al workers. The effectiveness of proposed a new interior design scheme of craft gallery was evaluate with different significant research. The evaluate outcome indicate an increase in response and decrease inattention in error response. Lately, there are many gallery in Malaysia especially in the suburban area were having problem of design issue. However, the Malaysian government was putting effort to settle the problem by renovation on the place and changing it to the new galleries with the environmental design. In the other side, the choice on renovation new galleries on the other place gives a lot of advantages to the people not only the client but also people surrounded by the galleries. For client, it one of the reason to attract more customers and making more income in business journey. If it happens, one of the issues could be settling by making a bigger space to let all the product could be display in proper arrangement. In conclusion, the suggestion on proposed new gallery in Bangsar was a great effect to make client to achieve the entire goal likes create the nature welcoming environment suitable with product and provide the systematic flow of space to make easier for customer